2021
DOI: 10.1186/s12903-021-01761-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical strain on periodontal ligament fibroblasts in presence of Aggregatibacter actinomycetemcomitans lysate

Abstract: Purpose Many adult orthodontic patients suffer from periodontitis, which is caused by oral pathogens such as the gram-negative Aggregatibacter actinomycetemcomitans (Agac). Like orthodontic tooth movement, periodontitis is associated with inflammation and alveolar bone remodelling thereby affecting orthodontic treatment. Interactions of both processes, however, are not sufficiently explored, particularly with regard to oxidative stress. Methods Aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We believe that the enhancement of anaerobic oxidation and the fragmentation of mitochondria are consistent with the adaptive protective response of PSCs under external stimulation to achieve stem cell maintenance. As for the alteration of ROS production under mechanical force, we found that the results of other researchers are inconsistent, which may be attributed to the divergent parameters of the force-loading [ 36 , 37 ]. Our findings may be affected by limitations such as the monotonous experimental condition of a single type of mechanical force.…”
Section: Discussionmentioning
confidence: 83%
“…We believe that the enhancement of anaerobic oxidation and the fragmentation of mitochondria are consistent with the adaptive protective response of PSCs under external stimulation to achieve stem cell maintenance. As for the alteration of ROS production under mechanical force, we found that the results of other researchers are inconsistent, which may be attributed to the divergent parameters of the force-loading [ 36 , 37 ]. Our findings may be affected by limitations such as the monotonous experimental condition of a single type of mechanical force.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, proinflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor alpha (TNFα) are produced by periodontal ligament cells on orthodontic mechanical force application and also when stimulated by the lipopolysaccharide of P. gingivalis and A. actinomycetemcomitans (68)(69)(70). Additionally, activation of key orthodontic bone remodeling pathway of receptor activator of nuclear factor -κB (RANK) and its ligand (RANKL) is modulated both by mechanical and bacterial stressors (71,72). Thus, expression of many of the biological mediators of orthodontic tooth movement can be potentiated by interactions between the orthodontically applied mechanical force and microbiome physiology.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some researchers pointed out that periodontal tissue produces NO under the action of orthodontic force. The precursor of NO accelerates OTM in rats and increases the number of osteoclasts and Howship's lacuna in the compression area, whereas NOS inhibitors that suppress NO production reduce OTM [6][7][8]. As a result, NO also has a significant impact on OTM.…”
Section: Introductionmentioning
confidence: 99%